Influence of flood‐stress on ambrosia beetle host‐selection and implications for their management in a changing climate. (30th August 2012) - Ranger, Christopher M.; Reding, Michael E.; Schultz, Peter B.; Oliver, Jason B.
<x xml:space="preserve">Abstract</x> 1 Xylosandrus germanus (Blandford) is a key pest of ornamental nursery trees. Ethanol is the most attractive semiochemical known for X. germanus, and its emission from trees represents a primary host‐selection cue. Ethanol production is induced by a variety of abiotic and biotic stressors, which could thereby predispose trees to attack by ethanol‐responsive ambrosia beetles. 2 To better understand X. germanus host‐selection behaviour within ornamental nurseries, a series of experiments examined the influence of flood‐stress on the attractiveness and susceptibility of flowering dogwood Cornus florida L. Under field conditions, more X. germanus were attracted to experimentally flood‐stressed dogwoods than neighbouring nonflooded controls in 2009, 2010 and 2011. Flood‐stressed dogwoods were also preferentially attacked in 2009–2011, although no attacks occurred on any of the neighbouring nonflooded trees. 3 Solid‐phase microextraction‐gas chromatography‐mass spectrometry detected ethanol in stem tissue from flooded dogwoods but not nonflooded trees. Acetaldehyde, acetic acid and ethanol were also emitted from the outer bark of flooded dogwoods but not nonflooded trees. 4 These results demonstrate that X. germanus preferentially lands on and attacks physiologically‐stressed hosts, and further support the role of ethanol in mediating this interaction. 5 Attacks by X. germanus have previously been suspected to occur on trees viewed as 'apparently‐healthy', although the possibility of such trees being in apparently‐stressed at the time of attack cannot be ruled out given the results obtained in the present study. Minimizing the impact of stressors known to induce the production of ethanol should be the primary foundation of a management plan for X. germanus and other ethanol‐responsive ambrosia beetles.